Colonización micorrícico arbuscular de Alnus acuminata Kunth en el noroeste Argentino en relación a la estacionalidad ya los parámetros edáficos - Becerra, Alejandra Gabriela (2007)
The objective of this study was to determine patterns of arbuscular mycorrhizal (AM) colonization of Alnus acuminate Kunth at two natural forests in relation to soil parameters at two different seasons (autumn and spring). The soil parameters studied were field capacity, pH, electrical conductivity, available P, total N and organic matter. The percentage of AM colonization was estimated and correlated to soil properties and to two different seasons. The results indicate that the percentage of AM colonization varied among soil types and was higher in spring than autumn. A significant positive correlation was found between AM colonization and electrical conductivity, organic matter and total Nitrogen. Results of this study provide evidence that AM colonization of A. acuminata can be affected by some soil parameters and seasonality. Key words. Alnus, arbuscular mycorrhizal, seasonality, soil type, Yunga forest.